Facial Palsy in an Extremely Low Birth Weight Neonate due to Acute Suppurative Otitis Media - Rachana RD; Rajendra Prasad Anne; Sai Kiran Deshabhotla; Tejo Pratap Oleti (Dr. Annil Mahajan, 2022)
We report an extremely low-birth-weight neonate with new onset unilateral facial palsy on ninth day of life. The child had neonatal sepsis, meningitis was ruled out and ear discharge was noted from the ipsilateral ear. Otoscopy suggested acute suppurative otitis media, while magnetic resonance imaging was suggestive of mastoiditis. The facial weakness improved with physiotherapy over next two weeks.